Content Of The Development Of Reflexive Competency Of Teachers Of Future Professional Education On The Basis Of An Integrative Approach - Hayitov A.I. (Periodica Journal, 2024)
This article talked about the content of the development in future professional education teachers of extremely necessary reclexive competence in professional activities on the basis of an integrative approach in higher education classes
Keywords: future vocational education teacher; integration; integrative approach